2012
DOI: 10.4103/0970-9290.111267
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparison of microleakage of two self-etched adhesive and the one-bottle adhesive used in pit and fissure sealant with or without saliva contamination

Abstract: The best technique of sealant therapy in saliva contaminated and non- contaminated condition is the use of acid-etching and bonding agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Similar to the results of the SBS analysis, the microleakage results in the EG were inferior (12.8%); in contrast, in the CG, little dye infiltration was observed (1.1%). A similar trend has been reported in the literature, in which a few studies have observed microleakage for the self-etch adhesive sealants in a range closer to that of acid-etch sealants 14,15) . However, extremely high microleakage values greater than those observed in our study have also been reported 16) .…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the results of the SBS analysis, the microleakage results in the EG were inferior (12.8%); in contrast, in the CG, little dye infiltration was observed (1.1%). A similar trend has been reported in the literature, in which a few studies have observed microleakage for the self-etch adhesive sealants in a range closer to that of acid-etch sealants 14,15) . However, extremely high microleakage values greater than those observed in our study have also been reported 16) .…”
Section: Discussionsupporting
confidence: 88%
“…They attributed the higher microleakage of self-adhesive composite to inability to eliminate the smear layer. Studies comparing the microleakage of selfetch and conventional etch and rinse adhesives have also mainly reported higher microleakage of self-etch adhesives at the enamel margins [25][26][27]. However, Vichi et al…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of the time of contamination during light curing was not considered in the Peng et al 15 and Memarpour et al [16] studies. Basir et al [17] carried out a study on the effect of the different adhesive system on fissure sealant microleakage with or without saliva contamination. They have reported that microleakage was reduced by using bonding systems, although it was not eliminated and sealants without any bonding agent could not tolerate slightest saliva contamination.…”
Section: Discussionmentioning
confidence: 99%